Does High-Risk Pool Coverage Meet the Needs of People at Risk for Disability? - Jean P. Hall; Janice M. Moore (SAGE Publishing, 2008)
State high-risk insurance pools serve people denied coverage because of pre-existing conditions. With benefit plans modeled on the individual market, these pools generally require higher out-of-pocket expenditures and provide fewer benefits than employer-sponsored plans, while their beneficiaries have very intensive needs. We profile 416 working adults enrolled in a state high-risk pool and document their health conditions and health care utilization. High-risk pool and federal employee benefits are compared to assess insurance structure and implications for health and disability outcomes.